Answer:
g(x) = (5x + 3)/ x - 7
Step-by-step explanation:
Let g(x) = y
y = (7x + 3)/x - 5
Make x the subject
xy - 5y = 7x + 3
xy - 7x = 5y + 3
x(y - 7) = 5y + 3
x = (5y + 3)/ y - 7
Therefore, the inverse of the function = (5x + 3)/ x - 7
Answer:
a y = 2
b.y = 14
c. y =56
Step-by-step explanation:
a .6 (1)- 4=2
y=2
b. 6 (3)- 4
=18-4
y=14
c. 6 (10) - 4
= 60 - 4 =56
Answer:
76
Step-by-step explanation:
4(-4(-9)-17)
4(36-17)
4(19)
Answer:
7x^3+46x^2-21x
"^" means exponet
Step-by-step explanation:
Answer:
Step-by-step explanation:
28 = 2 * 2 * 7
35 = 5 * 7
The common factor is 7 . This is the GCF
28 + 35 = 7(4 + 5) (answer)